A study on the sexual practices among selected young adults of Baranggay 3, Jaro, Leyte. - Acosta, Felice Sybil A.; Ranze, Doanne Jill T. (Tacloban City Felice Sybil A. Acosta, 2009)
The Study on the Sexual Practices Among Selected Young Adults of Barangay 3, Jaro, Leyte is aimed on finding out the actual sexual experiences, both practices and beliefs, among selected twenty randomly selected young adults aged 18-22 of Barangay 3, Jaro, Leyte who were identified through purposive sampling. Moreover, it is also intended to gather possible reasons of why they engage in such activities or practices; to identify the significant differences of the sexual behaviors among the male and female respondents and also to confer about some moral aspects regarding human sexuality. Further, an open-ended set of guide questions were utilized by the researchers for all interviews done.
There are eight sexual practices shared by the respondents that were categorized as penetrative and non-penetrative. Penetrative sexual practice is sexual intercourse while non-penetrative would include masturbation, petting, mouth-genital contact, necking, smack kissing, deep/French kissing and manual and oral stimulation of partner's genital. Surprisingly, only 15% of the respondents had used contraceptives. Majority of them applies the natural methods such as the withdrawal method and the calendar method. The data reveals that 95% of the respondents engage in the aforementioned sexual practices out of personal curiosity alone or out of personal interest. Only 5% of the respondents however, did it because of their partner's influence. Accordingly, one factor that influences them to engage in early sexual activity was that of the media such as pornographic videos and magazines. There was a significant difference between the males and females in the practice of masturbation which is genital manipulation. Twenty percent of the females engage in sexual activity and 100% among the males. Regret is a common after-effect among the females after having engaged in sex. Moreover, all of the respondents are actually aware that what they are doing and the things they have done sexually are morally wrong. Nonetheless, they still choose to engage in it. Knowing the fact that the young generations of today are already engaging in such sexual activities this early, there is a need for parents, schools and the government to do their part in reminding the young people of the health risks of sexual practices. Everyone must have the access to the right information about human sexuality. Media such as the television and most especially the internet must be monitored and limited to good and educative sights and shows. Peer counseling seminars are suggested to take place in the said locality to give emotional and psychological support to the young people.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science